Import Substitution: A Survey of Concepts, Measures and Models (The Pakistan Development Review, 1973)
The purpose of this article is to survey briefly the current literature on development planning and import substitution in order to put in perspective the various contributions to the subject. Section I surveys some of the aggregative models on import substitution; Section II brings out the impact of recent discussions on import substitution on the process of development planning; Section III contrasts the various treatments of imports in inter-industry anal¬ysis; and Section IV surveys some of the development planning models with similar structure or motivation.